Influence of reaction temperature and mixing intensity on fructo-oligosaccharides production - Mohd Ariff, Mohd Nor (2009)
This study investigates the influence of temperature and mixing intensity on the reaction of Ftase with sucrose. It is important in order to increase the efficiency of the fructo-oligosaccharides (FOS) production. FOS may highly contribute to the food industries, which give beneficial effect to diabetes and colon disease. The objective of this research is to determine the influence of temperature and mixing intensity on the FOS production. The conical flask and shaking water bath is used for the reaction of sucrose with Ftase. The process will be done by varying the temperature and mixing intensity respectively. For the first parameter, different temperature is used in this study which is 30°C, 40°C, 50°C, 60°C, 70°C, 80°C and constant mixing intensity of 100 rpm. For the second parameter, different mixing intensity is used which is 40 rpm, 60 rpm, 80 rpm, 100 rpm, 120 rpm,140 rpm and constant temperature of 65°C. All the samples are then heated up to 100°C to denature the enzyme activity. The samples are analyzed using UV-Vis spectrometer to measure the sucrose residual of the sample. The result of the experiment shows that the optimum condition of FOS production at 60°C and 60 rpm which is 40 g/L and 55 g/L of sucrose residual. From the experiment, it can be concluded the FOS production is increased from 30°C to 60°C, then decreased from 60°C to 80°C. Meanwhile the effect mixing intensity shows the FOS production is increased from 40 rpm to 60 rpm, then decreased from 60 rpm to 100 rpm before increased again from 100 rpm to 140 rpm.